Behavioral Counseling Guide Using Self-Management Techniques with the Help of the Trello Application to Increase Achievement Motivation - Ida Ayu Putu Prahasti Negari; I Ketut Gading; Nyoman Dantes; Ni Ketut Suarni (Bisma The Journal of Counseling, 2025)
National education emphasizes the importance of optimizing students’ potential through the enhancement of achievement motivation. However, many students continue to exhibit low motivation, as reflected in a lack of learning independence, a tendency to procrastinate, and high dependency on peer assistance. This study aims to develop and evaluate the effectiveness of a behavioral counseling guide using the self-management technique supported by the Trello application in improving students' achievement motivation. The method employed is Research and Development (R&D) using the 4D model (Define, Design, Develop, Disseminate). The trial subjects consisted of seven eighth-grade students identified as having low achievement motivation. The research instruments included a content validity sheet, a practicality questionnaire, and an achievement motivation questionnaire, all of which were tested for validity and reliability. The results indicate that the guide has high content validity, excellent practicality, and is significantly effective in improving students’ achievement motivation based on N-Gain and Wilcoxon test results. These findings suggest that the integration of digital-based self-management techniques is effective in fostering students’ self-regulation and can be replicated as an innovative counseling strategy to enhance students’ learning motivation in the digital era.